RISK ASSESSMENT OF INSURANCE SERVICES IN OUR COUNTRY - Sh. F. Kobilzhonova (American Journals, 2024)
Our country risk assessment reflects our opinion on the insurance risks to which the economy, politics, financial system, payment culture and the rule of law in the Republic of Uzbekistan are exposed. Our assessment of the sectoral risk of the Uzbek general insurance sector is in line with similar estimates for Kenya, Angola and India. However, the general insurance markets in these countries are at very different stages of development. Our opinion on the Uzbek general insurance sector takes into account the still developing institutional system, as well as the dynamics of the industry and the characteristics of insurance products.
Keywords: Insurance activity, insurance interest, insurance premium, insurance franchise, insurance market, insurance products, subrogation, acquisition, insurance contract, income, property, property interest, liability, insurance, policyholder, insurer